One chance - Gillmor Murphy, Emily, 1990- (Transworld Ireland, 2014)
What if your dream was against all odds? Liz O'Brien doesn't want to fall in love. All she has ever wanted is to be a professional show-jumper and now it's within her grasp. She'll do anything to succeed ...even if that means keeping secrets from those around her. Matt has no intention of falling in love, either. He has never known a thrill like show-jumping. Intense, exhilarating and fast-paced - for Matt, nothing beats the rush that comes with a win. But then Matt and Liz are thrown together as rivals, and as desire begins to take over, tension grows between them. Both must fight against all odds for their dreams - and for each other.